Causes, trends and implications of motorization in Malaysia - Kadar Hamsa, Abdul Azeez (2009)
Motorization trend has been rising rapidly in many countries including Malaysia. But the level and trend of motorization in each country varies according to major factors such as population, size of the country, economic growth, income level, fuel cost, and public policy on vehicle ownership. The level of motorization has both positive and negative impacts. On the positive side, it provides mobility from a landuse to another landuse to meet various purposes besides increasing trade related to transportation. On the negative side, it increases pressure on the environment by increasing more pollutants into the atmosphere causing global warming, traffic congestion, accidents, and added pressure on the road and rail infrastructure in terms of capacity. Looking at the past trend of motorization, the future appears very bleak. This paper highlights trends and causes of motorization in the past, its likely impact on the environment and possible implications.